Perancangan Dan Pengukuran Sistem Kinerja Lingkungan Untuk Mendukung Proper Pada Industri Gas - Anindita Etri Wulandari; Iwan Vanany (BISMA (Bisnis dan Manajemen), 2017)
Globalization effect and technology development which is accompanied by economic activity that involving the use of natural resources has created environmental issue in the oil and gas company. The issue of the environment is currently the main focus in improving concern for the environment and the improvement of the environmental performance of their company. PT X is a one of government company who has focus in midstream sector and downstream of gas industry in Indonesia has a role in gas trading, transportation, process and distribution. PT. X managing the gas transmission infrastructure in West and East Java, South and North Sumatra, Aceh and East Kalimantan. PT. X has mission to increase environmental performance through environmental friendly production process and reliable brand image. To accomplish their mission, these companies use ISO 14001: 2015 Environmental Management System and environmental company rating program (PROPER) as tools for environment performance evaluation but for measurement of the environmental performance, but PT X does not have the key of environment performance indicators (KEPI). Then, the result of KEPI identification used to design of the environmental performance system, which using methods for measurement such as Integrated Environment Performance Measurement System (IEPMS), Analytical Hierarchy Process (AHP), and Objective matrix (OMAX). Based on this research, there are 70 KEPI consisting of 51 KEPI quantitative and 19 KEPI qualitative. Total value of environment performance in PT. X is 5.86, which is categorized into yellow color which means the company needs intensive controlling and evaluating to increase the company environment performance.